2016
DOI: 10.12973/eu-jer.5.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Student Perception of Academic Achievement Factors at High School

Abstract: Measuring the quality of the 'product' is elemental in education, and most studies depend on observational data about student achievement factors, focusing overwhelmingly on quantitative data namely achievement scores, school data like attendance, facilities, expenditure class size etc. But there is little evidence of learner perceptions. 553 students from two different universities, who graduated from 3 high school types, were asked to respond to two fundamental questions to reflect on school and classroom le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, in this study, academic achievement is indicated by learners' competency in English Language. According to Bahar (2016), academic achievement can be affected or influenced by numerous factors including classroom atmosphere. Therefore, it is essential for teachers to do everything possible to ensure that school environment and classroom atmosphere, in particular, favors the interest of learners for maximized learning achievement to be realized.…”
Section: The Concept Of Academic Achievementmentioning
confidence: 99%
“…Therefore, in this study, academic achievement is indicated by learners' competency in English Language. According to Bahar (2016), academic achievement can be affected or influenced by numerous factors including classroom atmosphere. Therefore, it is essential for teachers to do everything possible to ensure that school environment and classroom atmosphere, in particular, favors the interest of learners for maximized learning achievement to be realized.…”
Section: The Concept Of Academic Achievementmentioning
confidence: 99%
“…Good study habits include time management, interest in class, completion of assignments or doing homework on time, following a study schedule and concentration etc. (Bahar, 2016). Study skills or habits represent rate of the involvement of students in their studies, regular review of academic tasks and material and ability to manage time properly to complete academic tasks (Crede & Kuncel, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When the students in a country fail to perform well in their academics the future of the country is considered ineffectual in terms of skilled man power. In Turkey, Bahar (2016) observed a massive failure of students in their academic achievement that posed a threat to the future labor market competencies. This also called for setting up of bodies tasked to inspect the causes of underperformance in Turkey.…”
Section: Introductionmentioning
confidence: 99%